STRATEGI KOMUNIKASI PEMASARAN MELALUI ENDORSEMENT FADIL JAIDI TERHADAP MINAT BELI KONSUMEN - Nisa, Lulu’ Khoirun; Saputro, Edy Purwo (Linimasa : Jurnal Ilmu Komunikasi, 2025)
This study analyzes the influence of endorsements by Fadil Jaidi on the social media platform Instagram on purchase intention toward the Nyemil Saji product. Employing a quantitative explanatory approach, the study examines the causal relationship between the endorsement variables—which include credibility, attractiveness, and content quality—and purchase intention, which comprises confidence, purchase decisions, desires and needs, and recommendations. Research data were collected through an online questionnaire completed by 99 respondents, all of whom are followers of the Instagram account @fadiljaidi. Regression analysis results indicate that endorsements by Fadil Jaidi have a positive and significant effect on purchase intention (regression coefficient = 0.803, p < 0.01). The endorsement variable explains 80.3% of the variability in public purchase intention (R² = 0.803). These findings reinforce the relevance of the Stimulus-Organism-Response (SOR) theory, wherein endorsements act as stimuli that shape consumer perceptions and drive purchasing decisions. From a practical perspective, the results of this study affirm the effectiveness of influencer-based marketing in increasing purchase intention, particularly for everyday consumer products. The implications of this research provide valuable insights for marketers in selecting credible endorsers who align with the target market to optimize digital marketing strategies.